The benchmark halo giant HD 122563: CNO abundances revisited with three-dimensional hydrodynamic model stellar atmospheres. Issue 3 (5th January 2018) - Collet, R; Nordlund, Å; Asplund, M; Hayek, W; Trampedach, R
Abstract: We present an abundance analysis of the low-metallicity benchmark red giant star HD 122563 based on realistic, state-of-the-art, high-resolution, three-dimensional (3D) model stellar atmospheres including non-grey radiative transfer through opacity binning with 4, 12, and 48 bins. The 48-bin 3D simulation reaches temperatures lower by ∼300–500 K than the corresponding 1D model in the upper atmosphere. Small variations in the opacity binning, adopted line opacities, or chemical mixture can cool the photospheric layers by a further ∼100–300 K and alter the effective temperature by ∼100 K. A 3D local thermodynamic equilibrium (LTE) spectroscopic analysis of Fe i and Fe ii lines gives discrepant results in terms of derived Fe abundance, which we ascribe to non-LTE effects and systematic errors on the stellar parameters. We also determine C, N, and O abundances by simultaneously fitting CH, OH, NH, and CN molecular bands and lines in the ultraviolet, visible, and infrared. We find a small positive 3D–1D abundance correction for carbon (+0.03 dex) and negative ones for nitrogen (−0.07 dex) and oxygen (−0.34 dex). From the analysis of the [O i ] line at 6300.3 Å, we derive a significantly higher oxygen abundance than from molecular lines (+0.46 dex in 3D and +0.15 dex in 1D). We rule out important OH photodissociation effects as possible explanation for the discrepancy and note that lowering the surface gravity would reduce the oxygen abundance difference between molecular and atomic indicators.